Exosomal microRNA⁃93⁃3p secreted by bone marrow mesenchymal stem cells downregulates apoptotic peptidase activating factor 1 to promote wound healing. Issue 1 (1st January 2022) - Shen, Caiqi; Tao, Changbo; Zhang, Aijun; Li, Xueyang; Guo, Yanping; Wei, Hanxiao; Yin, Qichuan; Li, Qiang; Jin, Peisheng
ABSTRACT: Wounds are soft tissue injuries, which are difficult to heal and can easily lead to other skin diseases. Bone marrow mesenchymal stem cells (BMSCs) and the secreted exosomes play a key role in skin wound healing. This study aims to clarify the effects and mechanisms of exosomes derived from BMSCs in wound healing. Exosomes were extracted from the supernatant of the BMSCs. The expression of the micro-RNA miR-93-3p was determined by qRT-PCR analysis. HaCaT cells were exposed to hydrogen peroxide (H2 O2 ) to establish a skin lesion model. MTT, flow cytometry, and transwell assays were conducted to determine cellular functions. The binding relationship between miR-93-3p and apoptotic peptidase activating factor 1 (APAF1) was measured using a dual luciferase reporter gene assay. The results showed that BMSC-derived exosomes or BMSC-exos promoted proliferation and migration and suppressed apoptosis in HaCaT cells damaged by H2 O2 . However, the depletion of miR-93-3p in BMSC-exos antagonized the effects of BMSC-exos on HaCaT cells. In addition, APAF1 was identified as a target of miR-93-3p. Overexpression of APAF1 induced the dysfunction of HaCaT cells. Collectively, the results indicate that BMSC-derived exosomes promote skin wound healing via the miR-93-3p/APAF1 axis. This finding may help establish a new therapeutic strategy for skin wound healing.